Development of the accounting system in the digital economy - Zh. M. Korzovatykh (Вестник университета)
The current processes of globalisation and digitalisation, the use of cloud technologies, artificial intelligence capabilities, robotics, big data and tools that allow large amounts of information to be processed in a short period of time by economic actors in their practical activities affect the conceptual basis of theoretical and methodological approaches to the organisation of the accounting system, fill the concept of “accounting” with new meaning. The purpose of this research paper is to assess the transformation of elements of accounting method under the influence of innovative digital technologies being introduced in the accounting process. The research methodology is based on the dialectical and empirical method. The article is devoted to the analysis of domestic and global trends in the accounting system development under the conditions of digitalisation of the processes of collection, consolidation and analysis of information on the activities of economic entities. The article considers the impact of the information potential of the existing economic space on the transformation of the methodological basis of accounting. In this regard, the modification of the theoretical and methodological approach of building an accounting system is a necessary step in the further development of accounting and in maintaining its relevance in competition with modern information systems.